Moral Law and Political Law in Greek Mythology: The Case of Prometheus - Fernández Agis, Domingo (2006)
The aim of this work is to offer the reader a tour through the most significant interpretations of the Prometheus myth, attempting to contribute  from their standpoint to the clarification of the relationship between moral law and political law. In especial, it aims to highlight in Prometheus’s attitude something that betrays the presence of a strongly individualized conscience, whose dictates lead him to clash with power in its highest expression. On the other hand, different interpretations of the Greek concept of law are examined, where its highest expression is indebted to the idea of destiny. Based on Law, a common order that connects gods and humans is established, although not with the same degrees of subjection.